Analysis of Pedestrian Facilities in Tambak Market Area, Cikande Banten Province - Telly Rosdiyani; Bambang Hariyanto; Nurfadilah Nurfadilah (STMIK Dharma Wacana, 2025)
Pedestrian lanes or sidewalks are a place for pedestrians to carry out activities to provide services to pedestrians to feel safe, comfortable and avoid the risk of motor traffic. This study aims to maintain the characteristics of pedestrian movement, find out the level of pedestrian services on Cikande Pond Road, find out efforts that can be made to improve pedestrian road services on Cikande Pond Road. The method used was based on the 1995 Highway guidelines and the distribution of questionnaires to obtain respondent preferences. Results are obtained. Flow on the right side is 8.33 pedestrians/m/min while on the left side is 5.20 pedestrians/m/min, pedestrian speed is 37.62 m/min, Average Space Speed (Vs) is 3.322 m/min, density on the right side is 2.508 pedestrians/m2 while on the left side is 1.565 pedestrians/m2, space (Space) on the right side is 0.399 m2/ped while on the left side is 0.639 m2/ped, the pedestrian ratio on the right side is 0.111 while on the left side is 0.069, the service level (LOS) includes the